2020
DOI: 10.1186/s12967-020-02568-6
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic administration of human umbilical cord-derived mesenchymal stem/stromal cells for bronchopulmonary dysplasia: preliminary outcomes in four Vietnamese infants

Abstract: Background Bronchopulmonary dysplasia (BPD) is a severe condition in premature infants that compromises lung function and necessitates oxygen support. Despite major improvements in perinatal care minimizing the devastating effects, BPD remains the most frequent complication of extreme preterm birth. Our study reports the safety of the allogeneic administration of umbilical cord-derived mesenchymal stem/stromal cells (allo-UC-MSCs) and the progression of lung development in four infants with established BPD. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 39 publications
0
23
0
1
Order By: Relevance
“…However, the use of PBS, M199, culture media and DMEM are inappropriate for clinical and therapeutic treatment because they are not approved vehicles for safe infusion into patients. Therefore, in our study, NaCl and RL were chosen as the main base media for MSC preservation because they have been widely used in numerous clinical trials 3,8,21 . It was reported that MSCs maintained in saline or dextrose for more than 2 h exhibited significantly reductions in viability, CFU capacity and differentiation ability 22 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the use of PBS, M199, culture media and DMEM are inappropriate for clinical and therapeutic treatment because they are not approved vehicles for safe infusion into patients. Therefore, in our study, NaCl and RL were chosen as the main base media for MSC preservation because they have been widely used in numerous clinical trials 3,8,21 . It was reported that MSCs maintained in saline or dextrose for more than 2 h exhibited significantly reductions in viability, CFU capacity and differentiation ability 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in our study, NaCl and RL were chosen as the main base media for MSC preservation because they have been widely used in numerous clinical trials. 3 , 8 , 21 It was reported that MSCs maintained in saline or dextrose for more than 2 h exhibited significantly reductions in viability, CFU capacity and differentiation ability. 22 Based on the theory of cell ion and osmotic homeostasis, cell viability is strongly regulated by the osmolality and electrolyte concentration of the extracellular environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The xeno-free and serum-free medium PS has been used to manufacture ADMSCs and umbilical cord-derived MSCs in some clinical trials [34,40,41]. However, there is only limited data reporting the immunophenotype of MSCs in this medium so far.…”
Section: Discussionmentioning
confidence: 99%
“…Univariate analyses were conducted using Spearman's rank correlation and Kruskal-Wallis test. Statistical analyses were performed using the R software version 3.6.1 by a statistician [39]. Plots were prepared using the software GraphPad Prism 5.0 (GraphPad Software, La Jolla, CA).…”
Section: Discussionmentioning
confidence: 99%